Influence of environmental and anthropogenic factors on forest patch composition and structure in North Wollo Zone, Amhara region, Ethiopia - Mulugeta Alemu; Bikila Warkineh; Ermias Lulekal; Zemede Asfaw (PLoS ONE, 2025)
Ethiopia’s vegetation is increasingly threatened by anthropogenic activities and natural factors, leading to forest degradation and fragmentation. This study analyzed the composition and structure of woody species in the Gerado, Micha, and Mekelet forest patches in the North Wollo Zone, Ethiopia. Data were collected from 95 systematically laid plots (20 x 20 m²) along elevation gradients, sampling trees and shrubs with a diameter at breast height (DBH) ≥ 2.5 cm and height ≥ 2 m. Species diversity and richness were assessed using the Shannon-Wiener diversity index, while plant communities and their relationships with environmental variables were analyzed using hierarchical clustering and Redundancy Analysis (RDA) in R software. A total of 55 woody species, from 46 genera and 31 families, were recorded. Fabaceae was the most species-rich family (12 species). Four distinct plant community types were identified (R = 0.4703, p ≤ 0.001), with altitude, slope, and tree cutting significantly influencing community composition (p ≤ 0.05). The dominant species across all patches were Dodonaea viscosa subsp. angustifolia, Olea europaea L. subsp. cuspidata, and Vachellia sieberiana. Anthropogenic disturbances, such as tree cutting, firewood collection, charcoal production, and grazing, were key factors affecting vegetation structure. The findings highlight the need for community-based conservation strategies tailored to the unique ecological and socio-economic conditions of each forest patch to improve ecosystem resilience and sustainability.